2022
DOI: 10.2147/ccid.s378106
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of Early Short-Course, Moderate- to High-Dose Glucocorticoids for the Treatment of Stevens–Johnson Syndrome/Toxic Epidermal Necrolysis: A Retrospective Study

Abstract: To summarise the clinical characteristics of patients with Stevens-Johnson syndrome/toxic epidermal necrolysis syndrome (SJS/TEN) and analyse the efficacy and safety of systemic glucocorticoid therapy. Methods: This study was a retrospective study of 56 patients with SJS/TEN who had been systematically treated with glucocorticoids in the dermatology ward of Peking University Third Hospital from 2010 to 2020. The clinical characteristics, treatment regimen, effects on underlying diseases, incidence and outcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Short-term application of medium- to high-dose of systemic applications of glucocorticoids can effectively treat SJS/TEN with mild complications and little effect on underlying diseases. 29 It has been reported that corticosteroids and IVIG combination therapy has significant survival benefits for patients with SJS/TEN. 30 31 In our study, all patients were treated with glucocorticoids and more than half combined with IVIG; steroid pulse therapy was administered in severe and rapidly progressive cases.…”
Section: Discussionmentioning
confidence: 99%
“…Short-term application of medium- to high-dose of systemic applications of glucocorticoids can effectively treat SJS/TEN with mild complications and little effect on underlying diseases. 29 It has been reported that corticosteroids and IVIG combination therapy has significant survival benefits for patients with SJS/TEN. 30 31 In our study, all patients were treated with glucocorticoids and more than half combined with IVIG; steroid pulse therapy was administered in severe and rapidly progressive cases.…”
Section: Discussionmentioning
confidence: 99%
“…Findings may include skin and mucous membrane pain, erythema, blisters, epidermal exfoliation, and other skin lesions involving the conjunctiva, oral cavity, and/or urogenital mucosa. [ 6 ] Histopathologic examination, if chosen as a diagnostic modality, is characterized by extensive apoptosis and necrosis of keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, research on various communities demonstrate that the chance of developing SJS/TEN is maximum just after starting medication and declines after 8 weeks or longer of treatment [46]. It is noteworthy to note that long-term usage of glucocorticosteroids for a range of illnesses has no effect on the frequency of SJS/TEN incidence for the pharmaceuticals in question, but it seems that glucocorticoids increases the period between the commencement of drug consumption and the onset of SJS/TEN [47]. According to recent study on pediatric TEN, children may be more sensitive to acetaminophen than adults are and similar medications to those used in adults are being employed [48].…”
Section: Drugsmentioning
confidence: 99%